Diabetes and developing knowledge of the body. Issue 2 (February 1984) - Eiser, C; Patterson, D; Tripp, J H
Abstract : Fifty seven diabetic children were compared with healthy children for knowledge of their bodies and causes of diabetes. Diabetic children were more likely to include the pancreas and less likely to include the brain or stomach in drawing their bodies. The data have implications for understanding how illness affects psychological development.